Features of the formation of hydrogen bonds in solutions of polysaccharides during their use in various industrial processes - Mank, Valeriy; Melnyk, Oksana (My University, 2011)
The paper studies the role of water in stabilizing the ordered structure of biological macromolecules methods of X-ray diffraction analysis, rheology , NMR and IR spectroscopy. The research results can be explained by sol-gel phase transition in solutions of polysaccharides, a significant increase in sorption capacity of these molecules to the surface of solutions of mineral adsorbents with increasing temperature in the purification of liquid foods (juices , alcoholic and soft drinks) , processes retrogradation biological molecules.
Keywords: natural polymers; ordered structure of biological macromolecules; hydrogen bonds; природні полімери; впорядкована структура біологічної макромолекули; водневі зв′язки; природные полимеры; упорядоченная структура биологической макромолекулы; водородные связи; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів; кафедра експертизи харчових продуктів